Trauma Reflected At Okky Madasari's Bound Novel(2013): A Psychoanalytic Approach - Fitriawan, Galih (2016)
The major problem in this study is how the major character proves his freedom and trauma in Bound novel by Okky Madasari. This study focuses on the one of the major characters namely Sasana, using the meaning of psychoanalytic analysis. The object of this study is Okky Madasari Bound novel published in 2014 by Gramedia pustaka. The type of this study is descriptive qualitative. The primary data source is the novel Bound itself and the secondary data sources are books or any information related to the practice of freedom, trauma and the moral problem that support the psychoanalytic approach by Sigmund Freud. The technique of analyzing data in this research paper is descriptive. The researcher concludes that freedom and trauma is the individual emotions, it drives from system of personality. The psychological analysis shows that person's switched their identities coming from his id and fictional ego has pushed his to do some efforts to attain the superego and he must sacrifice everything. Finally, the psychological analysis shows that the human factor will exchange their characters because the activating personality aspects within the characters and the cause are among other family and environmental factors. Okky Madasari gives the important points when the major character, Sasana, gets the conflict between his id and superego to prove his freedom.The outcome of the study shows that the problem faced by the major character Sasana causes the conflict of his mental condition. It comes because he struggles to prove his freedom and the trauma for his life. Finally, his effort makes him suffer until the end. Keywords: Trauma, Bound, Psychoanalytic Approach.